Decreased subfoveal choroidal thickness and failure of emmetropisation in patients with oculocutaneous albinism - ÇERMAN, EREN; ÇELİKER ATABERK, HANDE; ELÇİOĞLU, HURİYE NURSEL; ERASLAN, MUHSİN; ŞAHİN, ÖZLEM (BMJ PUBLISHING GROUP, 2014)
Purpose The purpose of this work was to describe the choroidal structure in patients with oculocutaneous albinism (OCA). Methods 20 eyes of 10 patients with OCA and 14 eyes of 7 healthy controls were recruited for the study. Enhanced depth imaging optical coherence tomography (OCT) images of the subjects were taken. The choroidal thickness (CT) was measured from the outer boarder of the retinal pigment epithelium to the inner boarder of sclera at 500 mm intervals of a horizontal section from the optic disc. Statistical analysis was performed to evaluate variations in CT at subfoveal and peripapillary areas. Results In the fundoscopic examination and OCT imaging, the foveal light reflex was absent and the foveal pit could not be observed in all of the patients with OCA. The mean subfoveal CT of the patients with OCA was significantly thinner (242 +/- 56 mu m) compared with healthy controls (349 +/- 70 mu m) (p<0.001); while there was no statistically significant difference in the peripapillary CTs of the patients with OCA and controls (157 +/- 42 mu m vs 151 +/- 31 mu m respectively, p=0.77), indicating a localised abnormality of choroidal anatomy. Conclusions This study for the first time demonstrated that CT is decreased in patients with OCA at the subfoveal region. These data combined with the underdevelopment of the foveal pit indicate that there is a generalised developmental or genetic abnormality in the posterior pole of patients with OCA. This choroidal structural abnormality might be related to the previously reported failure of emmetropisation in these children. Further research is needed to understand choroidal metabolism and its relationship with these anatomical changes in albinism.